ANALISIA REABILITAS (KEKUATAN DAN KEMUDAHAN) PADA SUBTITUSI “END CAP” DENGAN MENGGUNAKAN “END PLATE” PADA SPOOL UNTUK PENGETESAN PRE COMMISIONING – HYDRO TEST - Pasaribu, Ardiansyah (UNIMAR AMNI Semarang, 2025)
In the piping fabrication process and to meet the client’s requirements and specifications, hydrotest testing is needed to test the strength of the welding/connection process and test for leaks in the product or production output. Each testing stage definitely has obstacles, one of the obstacles that occurs ih Hydrotest work is the unavailability on the market of the material needed for the Pre Commissioning Test-Hydro Test, namely End Cap, to overcome this obstacle the engineering team recommends a substitute solution for “End Cap” by using “End Plate”. The research carried out will identify the suitability of the analyzes mentioned above. The research method is experimental with quantitative methods. The results of the research show that the substitution of using an End Plate for an End Cap is considered to have sufficient strength value in terms of strength, shows that the substitution of using an End Plate for an End Cap is stated to have a greater convenience value than using an End Cap in terms of ease of obtaining material, shows that the substitution of using an End Plate for an End Cap is stated to have a greated to have a greater convenience value than using an End Cap in terms of ease of installation/fit up and is stated to have a smaller convenience value than using an End Cap in terms of ease in the welding/welding process.